진단 지원 장치, 기계 학습 장치, 진단 지원 방법, 기계 학습 방법, 기계 학습 프로그램 및 알츠하이머 예측 프로그램 - SHIINO AKIHIKO (2023)
ADNC환자가 알츠하이머병을 발증할 가능성을 고정밀도로 예측한다. ADNC를 가지는 피험자가 사전 결정 기간 내에 알츠하이머병을 발증할 가능성의 예측을 실시하는 진단 지원 장치(2)로서, 기계 학습된 예측 알고리즘(D4)에 따라서 상기 피험자가 사전 결정 기간 내에 알츠하이머병을 발증할 가능성의 예측을 실시하는 예측부(23)를 구비한 진단 지원 장치(2). The possibility that an ADNC patient will develop Alzheimer's disease is predicted with high accuracy. A diagnosis assistance device 2 predicts a possibility that a subject who has ADNC will develop Alzheimer's disease within a prescribed period, the diagnosis assistance device 2 comprising a prediction unit 23 that predicts the possibility that the subject will develop Alzheimer's disease within a prescribed period, according to a machine-learned prediction algorithm D4.